Design and Synthesis of Conformationally Diverse Pyrimidine-Embedded Medium/Macro- and Bridged Cycles via Skeletal Transformation - Choi, Yoona; Lee, Subin; Kim, Heejun; Park, Seung Bum (Frontiers in Chemistry, 2022)
The rigidity and flexibility of small molecules are complementary in 3-dimensional ligand-protein interaction. Therefore, the chemical library with conformational diversity would be a valuable resource for investigating the influence of skeletal flexibility on the biological system. In this regard, we designed and synthesized ten conformationally diverse pyrimidine-embedded medium/macro- and bridged cyclic scaffolds covering 7- to 14-member rings via an efficient skeletal transformation strategy. Their high conformational and shape diversity was confirmed by chemoinformatic analysis.